Legal Policy of Legislation in the Field of Natural Resources in Indonesia - Hamzah, Herdiansyah (Hasanuddin Law Review, 2016)
Given the urgency for the peoplesâ€™ interests, legislation in the field of natural resources should be treated more compared to other fields. The urgency of arrangement in the field of natural resources is not only the right of every citizen to gain access to natural resources that we have, but also provide a guarantee that Indonesiaâ€™ natural resources can still be maintained and sustained to future generations. Unfortunately, the legal policy of natural resources tends to move towards free market competition, which is on one side open domination space for both private and foreign sectors, and on the other side attempted to remove the Stateâ€™s role in the control and management of natural resources. This was strengthened by some of legislation in the field of natural resources were canceled in part or in their entirety by the Constitutional Court. In consideration of the Constitutional Court decision, explicitly confirms that the legislation product in the field of natural resources does not comply to the conditionally constitutional, where the right to â€œthe control of stateâ€ of natural resources as mandated in Article 33 of the 1945 Constitution, is an absolute and should not be omitted. A shift in the law-political direction that tends to be pro-market, influenced by several aspects: First, the market ideology that is not prevented due to lack of firmness of attitude, principle independence and sovereignty politically by the lawmakers. Second, the inconsistent application of the Indonesia law ideal that embodied in the Pancasila, the 1945 Constitution, in any formulation of laws related to the management of natural resources. Third, still neglecting the peoplesâ€™ participation, which in the process of making laws relating to the management of natural resources, they are closed to the demands of the people, so it tends to be very elitist and unresponsive to the aspirations of the Indonesian peoples.